2018
DOI: 10.1021/acsinfecdis.7b00228
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Photo-Cross-Linkable Diaminoquinazoline Inhibitor for Target Identification in Plasmodium falciparum

Abstract: Diaminoquinazolines represent a privileged scaffold for antimalarial discovery, including use as putative Plasmodium histone lysine methyltransferase inhibitors. Despite this, robust evidence for their molecular targets is lacking. Here we report the design and development of a small-molecule photo-cross-linkable probe to investigate the targets of our diaminoquinazoline series. We demonstrate the effectiveness of our designed probe for photoaffinity labeling of Plasmodium lysates and identify similarities bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Furthermore, these compounds have been found to be orally efficacious in murine malaria models, inhibiting the blood stage of the disease including transmission . The scaffold of 498 was recently exploited to generate a photoaffinity probe, identifying 104 proteins as potential targets of off‐target binding sites of this class . Verma et al.…”
Section: Malariamentioning
confidence: 99%
“…Furthermore, these compounds have been found to be orally efficacious in murine malaria models, inhibiting the blood stage of the disease including transmission . The scaffold of 498 was recently exploited to generate a photoaffinity probe, identifying 104 proteins as potential targets of off‐target binding sites of this class . Verma et al.…”
Section: Malariamentioning
confidence: 99%
“…However, the degree of resistance to compounds 2 and 4 indicates that broad resistance mechanisms, such as Pfmdr1 amplifications, could be playing a role (28,29). Previous studies of a related 2,4-diamino quinazoline series indicated that histone lysine methyltransferases could be the target of these compounds; however, recent use of photo-cross-linkable probes indicated that the compounds bound to many targets, including redox and nucleosome proteins, as well as chaperones (31)(32)(33). In vitro activity of 2-anilinoquinazolines in other apicomplexan parasites.…”
Section: Resultsmentioning
confidence: 99%
“…Interacting proteins, now enriched, are prepared for liquid chromatography followed by mass spectrometry (LC/MS—MS) so they can be identified. Recently, an alkyne tag on a photoactivatable group-diaminoquinazoline compound probe was used to bind its molecular target via UV-activated click chemistry; LC/MS—MS identified 104 candidate target genes [ 27 ]. Because pull-downs can yield false positives through non-specific binding, they should also be used in competition assays.…”
Section: Affinity-based and Protein-stability Assays Can Directly Idementioning
confidence: 99%